Answer:
f⁻¹(x) = (x-3)²
Explanation:
We have given a function.
f(x) = √x + 3
We have to find inverse of above function.
f⁻¹(x) = ?
Putting y = f(x) in above equation, we have
y = √x + 3
We have to separate x from above equation.
Adding -3 to both sides of above equation, we have
y-3 = √x+3-3
y-3 = √x
Taking square to both sides of above equation, we have
(y-3)² = (√x)²
(y-3)² = x
Swapping above equation , we have
x = (y-3)²
Putting x = f⁻¹(y) in above equation, we have
f⁻¹(y) = (y-3)²
Replacing y with x , we have
f⁻¹(x) = (x-3)² which is the answer.